IMPLEMENTASI KAIZEN TERHADAP EFISIENSI BIAYA PRODUKSI PT. DASA ANUGERAH SEJATI ASIAN AGRI JAMBI - Yohendry Yohendry; Osrita Hapsara; Yunan Surono (Universitas Batanghari, 2017)
The company through Kaizen costing to eliminate inefficient activity activities that occur in the company's production process Here, it can be seen clearly the role of Kaizen implementation to Efficiency of Production Cost (represented by Production Yield, Labor Cost, Material Cost and Transport Cost). The analytical method used is descriptive analysis to reveal facts of the object researched and SEM Analisys. The results showed that (1) the characteristics of Muda, Mura, and Muri and Efficiency of Production Cost is good; and (2) Implementation of Muda, Mura, and Muri together have a positive and significant effect on Efficiency of Production Cost PT. Dasa Anugerah Sejati - Asian Agri Jambi by 83%. The remaining 17% is influenced by other factors not examined. Implementation of Muda, Mura, and Muri have a positive effect on Production Cost Efficiency, meaning that high Efficiency of Production Cost is influenced by high implementation of Muda, Mura, and Muri. Keywords: Kaizen Costing, Efficiency of Production Cost, Production Yield, Labor Cost, Matherial Cost, Transport Cost, Muda, Mura, and Muri